Barreras de acceso a la atención odontológica durante la primera infancia. Medellín, 2007 (2014)
ABSTRACT: In health systems, access refers to the organization of services to ensure entry into the system and treatment continuity. The objective of this study was to identify dental care access barriers in children under the age of six from the experience reported by mothers and caregivers. Methods: this was a descriptive study based on an individual semi-structured interview to 11 community mothers (caregivers) and group interviews with 37 biological mothers, of whom 20 participated in a second individual interview because they had attended dental consultation for their children in the past. Results: community mothers are important in identifying children’s oral problems but they consider that oral care demands are a responsibility of parents. Mothers value their children’s oral health but they do not demand health care due to the fear of a traumatic situation. Health institutions encourage health care demands at more advanced ages. Access to services is even harder for SISBEN members. Conclusions: during early childhood, children of lower socioeconomic levels face multiple barriers to dental care access. Even health insurance fails to guarantee access. The most frequent barriers are of economic nature, but there are also cultural barriers and those related to the system’s organization, such as children’s short age, often used by mothers and institutions as an excuse to avoid requesting or providing timely care.